2016
DOI: 10.1007/s12040-016-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irregularity on torsional surface waves in an initially stressed anisotropic porous layer sandwiched between homogeneous and non-homogeneous half-space

Abstract: The present paper is concerned with the propagation of torsional surface waves in an initially stressed anisotropic porous layer sandwiched between homogeneous and non-homogeneous half-space. We assume the quadratic inhomogeneity in rigidity and density in the lower half-space and irregularity is taken in the form of rectangle at the interface separating the layer from the lower half-space. The dispersion equation for torsional waves has been obtained in a closed form. Velocity equation is also obtained in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…BC3: The continuous conditions (Saha et al [11]) at the irregular surface, that is, z=εFr, are identified as normaliv2=v3; ()iiS()v2rgoodbreak−v2r()goodbreak−εF1+ε2F2goodbreak+()11+ε2F2Rv2zgoodbreak=()C44[]v3rgoodbreak−v3rgoodbreak+e15()φ3r()goodbreak−εF1+ε2F2goodbreak+()11+ε2F2()C44[]v3zgoodbreak+e15()φ3z; …”
Section: Boundary Conditions (Bcs) and Dispersion Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…BC3: The continuous conditions (Saha et al [11]) at the irregular surface, that is, z=εFr, are identified as normaliv2=v3; ()iiS()v2rgoodbreak−v2r()goodbreak−εF1+ε2F2goodbreak+()11+ε2F2Rv2zgoodbreak=()C44[]v3rgoodbreak−v3rgoodbreak+e15()φ3r()goodbreak−εF1+ε2F2goodbreak+()11+ε2F2()C44[]v3zgoodbreak+e15()φ3z; …”
Section: Boundary Conditions (Bcs) and Dispersion Equationmentioning
confidence: 99%
“…So, it is important to study the influence of these imperfect interfaces on the torsional phase velocity. Propagation characteristics of surface wave on different type of interfaces were studied by Zang and Shinozuka [6], Singh and Lakshman [7], Tomar and Kaur [8], Sahu et al [9], Singh and Sahu [10], Saha et al [11], Singh et al [12], and Pal et al [13].…”
Section: Introductionmentioning
confidence: 99%